2021
DOI: 10.3390/su13052628
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Direct Resource Requirements of Urban Horticulture in the United Kingdom: A Citizen Science Approach

Abstract: Interest in urban food production is growing; recent research has highlighted its potential to increase food security and reduce the environmental impact of food production. However, resource demands of urban horticulture are poorly understood. Here, we use allotment gardens in the United Kingdom to investigate resource demands of urban horticultural production across the country. We conducted a nationwide citizen science project using year-long allotment ‘diaries’ with allotment gardeners (n = 163). We analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
(72 reference statements)
3
13
1
Order By: Relevance
“…Pollard et al ( 2018a ) pointed out that there are not many articles focusing on the measurement of irrigation water consumption in UA, and Whittinghill and Sarr ( 2021 ) found that irrigation was the least-recorded practice among urban farmers and gardeners surveyed. Our results are largely consistent with the largest known survey to-date, a study of 163 allotment plots in the UK (Dobson et al 2021 ). While they found a much smaller average than ours overall (16 L/kg vs 71.6 L/kg), their findings were much closer to our average for individual gardens (16 L/kg vs 40 L/kg), which reflects our findings that individual gardens may use water more efficiently than collective gardens or urban farms, or they may simply under irrigate.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Pollard et al ( 2018a ) pointed out that there are not many articles focusing on the measurement of irrigation water consumption in UA, and Whittinghill and Sarr ( 2021 ) found that irrigation was the least-recorded practice among urban farmers and gardeners surveyed. Our results are largely consistent with the largest known survey to-date, a study of 163 allotment plots in the UK (Dobson et al 2021 ). While they found a much smaller average than ours overall (16 L/kg vs 71.6 L/kg), their findings were much closer to our average for individual gardens (16 L/kg vs 40 L/kg), which reflects our findings that individual gardens may use water more efficiently than collective gardens or urban farms, or they may simply under irrigate.…”
Section: Resultssupporting
confidence: 91%
“…It is perhaps not surprising, then, that our results are inconsistent with this limited literature. For example, Dosbon et al ( 2021 ) found an average of 1.9 L compost used/kg food in allotment plots, compared to a mean and standard deviation of 5.5±6.3 L/kg and median of 3.0 L/kg here for the 38 sites that used compost. On an area basis, these sites used an average of 9.7±11.5 L of compost/m 2 , with a median of 4.9 L/m 2 .…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…We highlight that our examples are focused on citizen science at the production, processing and consumption stages of the food system, with food system inputs (natural resources, manufactured inputs or human resources) all offering their own potential citizen science engagement opportunities. Indeed, examples of irrigation (Buytaert et al, 2014;Ramirez-Andreotta et al, 2015;Pérez-Belmont et al, 2019), fossil fuel (Zilliox and Smith, 2018) or other input-based citizen science are currently present in the literature (Dobson et al, 2021).…”
Section: Methodsmentioning
confidence: 99%